DILEMMAS OF WORKERS IN PANDEMIC TIMES: REPORTS FROM RIVERSIDE TEACHERS - Aldenora dos Santos Lima, Maria; Fernandes Sessa Mendonça, Gizeli; Aparecido Gonçalves, Israel (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to understand the main difficulties of riverside teachers in the municipality of Porto Walter (Acre), between the pandemic period of 2020 and 2021. The methodology is qualitative in that it was concerned with analyzing and interpreting particularities of riverside teachers, describing their complexities and, therefore, field research is combined with semi-structured interviews. The final considerations point to the great difficulties in bringing quality education to the most remote places in the country. In a country with gigantic territorial dimensions like ours, it is not easy to reach certain regions.